Pengaruh Metode Latihan ABC Run terhadap kemampuan Belajar Lari Sprint 100 Meter Siswa Pada Kegiatan Ekstrakurikuler Atletik Sekolah Menengah Pertama - Fiko Ramdhani; Rahmat Iqbal; Ega Trisna Rahayu (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to determine the effect of the ABC Run training method on increasing the 100 meter run for students at SMPN 3 Cikarang Utara in extracurricular activities. This study uses experimental methods and uses a quantitative approach. The number of samples of 18 students in extracurricular activities, with the sampling technique used is purposive sample. Based on the results of data processing that has been calculated and analyzed by the researcher, the answer to the hypothesis that has been previously proposed by the researcher has been obtained. The results and conclusions of the researchers on the 100 m run in extracurricular activities at SMPN 3 Cikarang Utara. There was an influence on the students' 100 m run through the ABC run exercise method in extracurricular activities. This is evidenced by the findings when extracurricular activities with the number running 100 m. In the application of the ABC run method of basic training in athletics, there is a significant influence in the 100 m running number on students' extracurricular activities. So that by using the ABC run training method, training activities become more effective and interesting. In addition, the ABC run training method is very good given to students who take part in extracurricular activities so that the training program given to students becomes more effective and discovers something new in the process of athletic extracurricular activities for students at SMPN 3 Cikarang Utara.